Dinamika Populasi Hama Kutu Kebul pada Beberapa Varietas Kedelai (Glycine max (L) Merrill) - Nurul Hidayah, Muhammad Taufik; Fitri, Silvia (Program Studi Agroteknologi, 2024)
This research aims to examine soybean varieties that are resistant to whitefly pest attacks. This research was carried out at the Jember State Polytechnic experimental field, Sumbersari District, Jember Regency which was carried out from March 18 to June 17 2023 at an altitude of ±103 meters above sea level. This research was carried out using a single variety factor consisting of the first variety, namely Malabar (M), the second variety Ringgit (R), the third variety Dega 1 (D), and finally the Wilis variety (W) as a comparison and using a Randomized Block Design (RAK) with four repetitions, variety resistance test using the Chiang and Talekar method. The data obtained was then analyzed using the ANOVA test using Excel, significantly different results were further tested with the 5% BNT test at the 0.05 level. The research results showed that the varieties that were resistant to whitefly pest attacks were the Malabar variety (M), the Ringgit variety (R), and the Wilis variety (W). Meanwhile, the variety that is included in the somewhat resistant category is the dega 1 (D) variety. It was seen that during the research there were a lot of whitefly pests attacking soybean plants on the dega 1 variety, even the low yields also showed that the dega 1 variety was somewhat resistant to aphid attacks. kebul and research needs to be done on other soybean varieties. The aim of this research is to determine the level of resistance of soybean varieties to whitefly pest populations.